Anticoagulant Therapy Is Associated With Decreased Long-Term Mortality in Splenic Infarction Patients: A Multicenter Study - Yen, Chieh-Ching; Wang, Chih-Kai; Chaou, Chung-Hsien; Chen, Shou-Yen; Lin, Jhe-Ping; Ng, Chip-Jin (Frontiers in Medicine, 2021)
Background: Patients with splenic infarction (SI) are associated with a prothrombotic state and are vulnerable to subsequent thromboembolic complications. However, due to its rarity, there is no established treatment modality in this population. We aimed to examine the effect of anticoagulant therapy in SI patients. Methods: We performed a multicenter retrospective cohort study of 86 SI patients. Patients were categorized as anticoagulant users and anticoagulant nonusers. The associations between anticoagulant therapy, all-cause mortality, thromboembolic events and bleeding events were evaluated. Results: Forty-five patients (52.3%) received anticoagulant therapy during the follow-up periods. The all-cause mortality rate was 6.86 per 100 patient-years. Anticoagulant therapy was associated with 94% improved survival (HR=0.06; Cl 0.007-0.48; p=0.008), while the risk factors for all-cause mortality were prior stroke (HR=13.15; Cl 2.39-72.27; p=0.003) and liver cirrhosis (HR=8.71; Cl 1.29-59.01; p=0.027). Patients with anticoagulant therapy had a higher event-free survival curve for thromboembolic complications (p=0.03) but did not achieve a significant difference after adjustment using the Cox regression model as a time-dependent covariate (HR=0.57; Cl 0.13-2.45; p=0.446). There was no significant difference in the risk of bleeding events between the groups (p=0.728). Conclusions: Anticoagulant therapy in patients with SI was associated with better survival and was not related to an increased bleeding risk.